586. The Aging Epidemic: Virologic Control, Immunologic Recovery, Treatment Regimens, and Clinical Outcomes Among Older Adults Living with HIV in Washington, DC. (26th November 2018) - Akselrod, Hana; Aldous, Annette; Parenti, David; Simon, Gary; ,
Abstract: Background: As the number of older people living with HIV (PLWH) in the US rises, there is a need to identify factors that lead to poorer clinical outcomes. This study aimed to identify age-based disparities in virologic, immunologic, and clinical disease control. Methods: We analyzed data from the DC cohort, a longitudinal observational cohort of patients receiving HIV care at 15 clinics in 2011–2016 in Washington, DC. We compared 608 patients aged ≥60 years with 832 patients aged 18–35 years. t -Test and Wilcoxon rank-sum test were conducted for continuous variables, and chi-square or Fisher's exact tests for categorical variables. Results: Older patients reported less MSM-related (25% vs. 60%, P < 0.0001) and more IDU-related (18% vs. 0.5%, P < 0.0001) HIV acquisition than younger patients. The proportion of older patients with CD4 >500 cells/μL was higher at enrollment (56% vs. 53%, P = 0.0067), but lower at CD4 nadir (18% vs. 21%, P < 0.0001) and at most recent recording (60% vs. 69%, P = 0.0003). Younger patients were more likely to have HIV VL >200 copies/mL at enrollment (35% vs. 11%, P < 0.0001), recently (18% vs. 6%, P < 0.0001), and peak VL >100, 000 copies/mL during the study period (15% vs. 4%, P < 0.0001). Viral re-emergence after initial suppression was less common in older PLWH overall (27% vs. 39%, P < 0.0001), but more common in older patients infected for ≥10 years (29% vs. 22%, P = 0.0607). There was a shift toward novel ART regimens (TAF and INSTI) during the study period, with more older patients on an INSTI by its end (59% vs. 50%, P = 0.0007). Among older patients, 23% had chronic kidney disease (CKD), and 24% had a serum creatinine rise of ≥150% during the study period. Of patients with CKD, 16% remained on TDF. The incidence of malignancies during the study period was 3.5% among younger and 14.3% among older patients). These were mainly (92.2%) non-AIDS-defining cancers. Conclusion: Older PLWH in DC have a high burden of complications related to renal dysfunction, lower CD4 counts, and non-AIDS-defining malignancies; those with longer duration of infection also had more viral re-emergence. Opportunities to improve care include closer monitoring for resistant virus and new cancers, and consideration of ART regimens with high efficacy and better renal safety profiles. Disclosures: All authors: No reported disclosures.